Teachers Attitudes and Perception Towards the Implementation of Gifted Education Programme in North Central Nigeria. - Unegbu, Justina I.; Jonathan, Thani (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
Given that most teachers have one of the most significant influences on the educational development of gifted students, reports of negative attitudes and beliefs in popular misconception about giftedness are cause for concern. It is important to understand teachers’ perception and beliefs to implement effective training and educational practices to improve education for gifted students. The study focuses on teachers’ perception and attitude towards the implementation of gifted education programme in North Central Nigeria. A cross – sectional survey design was used. I59 teachers from Federal Government Academy Suleja and School for the Gifted Gwagwalada were used for the population. Questionnaire and Rating Scale were used for the instruments. the result shows that teachers perception and attitudes towards the implementation of gifted education tends to be high and at such enhances gifted education programme. Based on the findings, some recommendations were made such as, government should improve the condition of service of teachers in terms of regular payment of salary, promotion. These will enhance gifted education practices in Nigeria. Keywords: Perception, Attitude, Gifted Students, Teachers of the Gifted Students.